(untitled) (The Shivapuri Journal, 2026)
This article examines the relevance of the Gerasimov Doctrine as an analytical lens for understanding hybrid warfare and its implications for the Nepali Army. Although the concept emerged from a Russian strategic context, its emphasis on the integrated use of non-military instruments, information dominance, and indirect coercion offers useful insights into contemporary conflict dynamics confronting vulnerable states. Twenty-first-century warfare increasingly extends beyond conventional military confrontation, unfolding across informational, cyber, economic, and psychological domains. For small, non-aligned states such as Nepal, these multidimensional threats present complex challenges that traditional defense frameworks are often ill-equipped to address. Through a qualitative analysis of Nepal’s security environment, institutional arrangements, and recent crisis experiences, based on government policy documents, military and security reports, and other secondary sources, the study offers a Nepal-specific analysis of hybrid threats - defined as the coordinated use of military and non-military means by state or non-state actors to exploit vulnerabilities below the threshold of open conflict - that has received limited attention in existing literature. The analysis shows that Nepal’s experiences with disinformation campaigns, cyber incidents, economic pressure, and contested narratives are not isolated occurrences but part of broader patterns of hybrid conflict. Drawing on comparative security literature and Nepal’s own strategic constraints, the article proposes context-specific reforms, including the formulation of a hybrid warfare doctrine, strengthening of cyber and information operations capacity, improved intelligence integration, reform of officer education, and initiatives to enhance societal resilience. The study concludes that protecting Nepal’s sovereignty in the evolving security environment requires a strategic shift toward anticipatory, multi-domain defense grounded in whole-of-government coordination and strengthened civil-military synergy.